The Influence of Promotions and Consumer Satisfaction on Purchasing Decisions at PT Papparich Sun Plaza Medan - Sri Rezeki; Agus Rahmadsyah (Outline Publisher, 2023)
This study discusses the promotion and customer satisfaction of purchasing decisions at PT Papparich Sun Plaza Medan. The research methodology used is quantitative descriptive method. The type of data used in this study is quantitative data, which is obtained in the form of numbers and numbers. The population in this study supports 51,016 consumers and the sample in this study supports 100 consumers. Data analysis using multiple linear regression analysis methods. The analysis results provide an equation. Research Results Promotional Research and Customer Satisfaction of Purchasing Decisions at PT. Papparich Sun Plaza Medan. Rating with multiple regression analysis namely Purchasing Decision = 18,480 + 0,228 Promotion + 0,279 Consumer Satisfaction + e. The results of testing the Promotion and Customer Satisfaction hypothesis regarding the positive and significant of the Purchasing Decision at PT Papparich Sun Plaza Medan. The magnitude of the coefficient of determination is 0.414 means that the Promotion Strategy and Consumer Satisfaction can explain the Purchasing Decision at PT Papparich Sun Plaza Medan by 41.4% and the remaining 58.6% is supported by other variables outside of this study such as service quality, price, and product .